Report of the American Accounting Association Committee on International Accounting Operations and Education 1975-76. (The Accounting Review, 1977)
This article presents the text of a report by the Committee on International Accounting Operations and Education of the American Accounting Association (AAA) for 1975 to 1976. The 1974-75 Committee on International Accounting made an in-depth survey of corporate financial reporting by selected foreign companies in six foreign countries. The Report of that Committee suggested the continuation of this form of comparative study and the use of such material as a benchmark for measuring changes in financial reporting. The 1973-1975 Committee on Accounting in Developing Countries, in its Report, directed attention to the accounting education needs of developing countries and the Report proposed initiatives to be taken by the AAA for serving those needs. The study of comparative accounting systems is lagging behind the developments in other areas of the social sciences. The research which has been done to this point in time is simply descriptive of accounting practices in different countries. But there is now an impetus for more rigorous work in the area of comparative accounting.